Audit Quality: Fees, Tenure, and The Role of Firm Size Moderation - Shabira, Adelia Rahma; Aviyanti, Richo Diana; Alghizzawi, Moawiah (KEUNIS, 2025)
The audit aims to assurance of financial statements made by management. Agency theory states that management as a party that has more information than the principal is considered able to carry out moral hazard actions. Therefore, the audit results can be used by the principal to help assess the performance of the agent. The audit results are also considered as a positive information signal for the financial statements.Audit quality can be positive information for shareholders regarding management performance and integrity. Therefore, This study is credited with determining the influence of audit fees and tenure audits on audit quality by moderating by company size. The research uses a positive paradigm quantitative method. The research population is real estate companies listed on the IDX in 2018-2023, a total of 85 sampling techniques using purposive sampling, a sample of 45 was obtained with 225 observation data. Data analysis uses logistic regression. The results showed that audit fees had a positive effect on audit quality, audit tenure had no effect on audit quality and company size did not modify the influence of audit fees on audit quality and did not moderate the influence of audit tenure on audit quality.Quality audits can be the basis for decisions to assess management performance and reduce conflicts of interest.